Global influence of inventions and technology sovereignty - Elisabeth Mueller; Philipp Boeing (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
We study the technology sovereignty of Europe, the US, China, Japan, and Korea. By examining citations from PCT patents filed from 2000-2020, we assess the bilateral and global influence of inventions. We highlight four insights. First, the US shows superior technology sovereignty through its leadership in bilateral and global influence. Second, the US and Europe are highly integrated, but their global positions differ due to Europe's bilateral dependence on all countries except China. Third, while Japan has shown a recent decline from its former leading position, Korea has maintained its global influence. Finally, although China has filed the most patents in recent years, its dependence on all other countries amounts to the highest global dependence.
Keywords: O33; O34; 330; technology sovereignty; bilateral and global influence of inventions; patents and citations